Pengaruh Digital Marketing dan Harga Terhadap Keputusan Pembelian Ninda's Cake di Toapaya Kabupaten Bintan - Nur Sabila; Kamaruzaman (EMASHA: Jurnal Ekonomi, Manajemen dan Akuntansi Syariah, 2025)
Abstract This study aims to analyze the influence of digital marketing and price on the purchasing decisions of Ninda’s Cake products in Toapaya Bintan. With the increasing use of the internet and the development of Industry 4.0, digital marketing tool to enhance sales. This research employs a quantitative method with data collection through questionnaires distributed to 82 respondents who are consumers of Ninda’s Cake. The analysis results indicate that digital marketing has a positive and significant effect on purchasing decisions, with a t-value of 5,012 and a significance level of 0,000. Additionally, price also has a positive and significant effect on purchasing decisions, with a t-value of 3,616 and a significance level of 0,001. The F-test shows that simultaneously, digital marketing and price have a positive and significant effect on purchasing decisions, with an F-value of 98,731 and a significance lavel of 0,000. The coefficient of determination (R2) indicates that 70.7% of the variation in purchasing decisions can be explained by the variables of digital marketing and price. This research provides important contributions to the development of marketing strategies in the MSME sector, particularly in the food and beverage industry, and offers insights for business actors to enhance purchasing decisions through effective digital marketing and appropriate pricing strategies.